2014
DOI: 10.1155/2014/169459
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Electric, Magnetic, and Electromagnetic Fields on the Circadian System: Current Stage of Knowledge

Abstract: One of the side effects of each electrical device work is the electromagnetic field generated near its workplace. All organisms, including humans, are exposed daily to the influence of different types of this field, characterized by various physical parameters. Therefore, it is important to accurately determine the effects of an electromagnetic field on the physiological and pathological processes occurring in cells, tissues, and organs. Numerous epidemiological and experimental data suggest that the extremely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
60
0
5

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(74 citation statements)
references
References 145 publications
(161 reference statements)
0
60
0
5
Order By: Relevance
“…17 Some animal and human studies support neurochemical effects of weak electromagnetic fields that may act on neurotransmitters such as melatonin, cortisol, serotonergic and dopaminergic systems implicated in the pathophysiology of migraine. 3,23,36 Many electrophysiological studies in migraines often showed high power and asymmetry in the low EEG frequency band due to the reduction of the cholinergic activity of the brainstem that induces dysrhythmia in the thalamocortical pathway. 11,37 On the other hand, an electromagnetic field with a frequency of 10 Hz reduced the alpha band of the EEG.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17 Some animal and human studies support neurochemical effects of weak electromagnetic fields that may act on neurotransmitters such as melatonin, cortisol, serotonergic and dopaminergic systems implicated in the pathophysiology of migraine. 3,23,36 Many electrophysiological studies in migraines often showed high power and asymmetry in the low EEG frequency band due to the reduction of the cholinergic activity of the brainstem that induces dysrhythmia in the thalamocortical pathway. 11,37 On the other hand, an electromagnetic field with a frequency of 10 Hz reduced the alpha band of the EEG.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 The International Headache Society introduced refractory migraine (RM) into the International Classification of Headache Disorders 3 (ICHD-3 beta and 2 (ICHD-2) with a prevalence of 5%. [3][4][5] RM characteristics include chronic migraines or migraines without an aura, that significantly interfere with the quality of life in spite of preventive medications. 3,4 Many studies suggest that there are various causes behind migraines such as dysfunction within certain voltage channels in the CNS, neural regulation of the brain stem and cerebral circulation.…”
Section: Introductionmentioning
confidence: 99%
“…Ultimately, in light of the present literature, the melatonin hypothesis stating that disruption of melatonin secretion is a main factor in the carcinogenic effects of magnetic fields is not supported by either epidemiological or experimental data (Lewczuk et al, 2014), and thus should be regarded as negatively corroborated and rebutted (Vanderstraeten et al, 2012). Furthermore, the core of the original hypothesis was conceived on the potential association between ELF-MF and breast cancer (Stevens, 1987), which has also been dismissed (Feychting, 2013).…”
Section: Mechanism 1131 the Melatonin Hypothesismentioning
confidence: 93%
“…Influence of electromagnetic field on biological systems has been reported in many investigations [1][2][3]. Commonly, electromagnetic fields have been used in diagnosing and treating medical therapies [4].…”
Section: Introductionmentioning
confidence: 99%